The Relationship between Age and Impulsive Purchasing in Sri Lanka - Fernando, Charith Hubert (2013)
The effect of age on impulsive buying has been extensively researched in the developed economies and to a limited extent in developing economies. However such research is not available for countries like Sri Lanka, which are experiencing a period of stability and economic growth following three decades of civil conflict that has had significant bearing on the population’s social behaviour. This research is an attempt to study the effect of age on factors that influence impulsive purchasing in an urban middle class population of Colombo. The influence of age on impulse buying behaviour and the effect of age on the personal, product, marketing and socio-cultural factors influences on impulse buying were also investigated.The research was carried out by interviewing 30 interviewees. A two part semi-tructured questionnaire was used: the first part to gather demographic information, and the second part to gain insight into the relationship between age and impulsive buying. Additional questions were asked where clarification was necessary. 28 of the interviews were digitally recorded for later transcription and analysis. The study suggests that there is a negative relationship between age and impulse buying. The study also suggests that age impacts many of the personal, product marketing and socio-cultural factors that influence impulse buying behaviour, some of them have a positive relationship while others have a negative relationship.